Quadratus lumborum block: are we aware of its side effects? A report of 2 cases - Sá,Miguel (2018)
Abstract Background and objectives The quadratus lumborum block was initially described in 2007 and aims at blocking the same nerves as the ones involved on the Transverse Abdominis Plane block, while accomplishing some visceral enervation as well due to closer proximity with the neuroaxis and sympathetic trunk. Given its versatility, we have successfully used it in a wide range of procedures. We report two cases where we believe the dispersion of local anesthetic is likely to have led to a previously undescribed complication. Clinical reports We report two cases in which we performed a quadratus lumborum type II block and general anesthesia for total gastrectomy and right hemicolectomy. There were no noteworthy events while performing the block and inducing general anesthesia, but within 30-40 min serious hypotension and tachycardia were noted. As other motives for hypotension were ruled out, the event was interpreted as block-induced sympatholysis due to cephalad dispersion of the local anesthetic to the paravertebral and epidural space, and successfully managed with ephedrine and increase of the crystalloid infusion rate. Conclusions The quadratus Lumborum block is safe to execute and provides effective abdominal wall and visceral analgesia. However, the possibility of eliciting undesired episodes should prompt caution when performing this block and practitioners should thereafter remain vigilant. Questions regarding ideal dosing, volumes, timing of block and pertinence of catheters remain to be answered.